2017
DOI: 10.1186/s13028-017-0284-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of blood sucrose as a screening test for equine gastric ulcer syndrome (EGUS) in adult horses

Abstract: BackgroundEquine gastric ulcer syndrome (EGUS) is common in adult horses, particularly those involved in performance disciplines. Currently, detection of EGUS by gastroscopy is the only reliable ante mortem method for definitive diagnosis; however it is unsuitable as a screening test because it is expensive, time consuming, and is not readily available to most veterinarians. Sucrose permeability testing represents a simple, economical alternative to gastroscopy for screening purposes, and the feasibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…A further study using sucrose permeability as a marker of gastric damage showed that phenylbutazone caused more gastric damage compared to equipotent doses of meloxicam. However, sucrose permeability did not correlate with plasma protein concentrations, and the clinical relevance of these findings is not fully understood, nor is sucrose absorption directly related to gastric pathology . In foals, the use of NSAIDs is often associated with clinically significant adverse events, especially in relation to gastric ulceration.…”
Section: Topical Nsaidsmentioning
confidence: 95%
“…A further study using sucrose permeability as a marker of gastric damage showed that phenylbutazone caused more gastric damage compared to equipotent doses of meloxicam. However, sucrose permeability did not correlate with plasma protein concentrations, and the clinical relevance of these findings is not fully understood, nor is sucrose absorption directly related to gastric pathology . In foals, the use of NSAIDs is often associated with clinically significant adverse events, especially in relation to gastric ulceration.…”
Section: Topical Nsaidsmentioning
confidence: 95%
“…Gastroscopy is currently the only reliable ante mortem means of diagnosing and monitoring EGGD; and should be considered the gold standard against which all other diagnostic tests are compared (Sykes et al, 2015a). Based on current evidence, the sucrose blood test and tests for protein or haemoglobin in faeces are unreliable and should not be used diagnostically (Sykes et al, 2014a;Hewetson et al, 2017). Biopsies are rarely indicated but if more severe pathological changes are suspected or if cases are refractory to treatment for 3 or more months then biopsies should be considered.…”
Section: Diagnosismentioning
confidence: 99%
“…ESGD is very common, particularly in performance horses (>80%) [5][6][7][8][9] and has potentially deleterious effects on both animal welfare and performance [3,4]. At present there are no reliable, noninvasive, rapid diagnostic tests available to detect ESGD [10][11][12], and the current consensus statement recommends gastroscopy as the most reliable diagnostic method [4,12,13]. However, gastroscopy, is unsuitable as a screening test due to it being expensive, time consuming, and not readily available to most veterinarians [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…At present there are no reliable, noninvasive, rapid diagnostic tests available to detect ESGD [10][11][12], and the current consensus statement recommends gastroscopy as the most reliable diagnostic method [4,12,13]. However, gastroscopy, is unsuitable as a screening test due to it being expensive, time consuming, and not readily available to most veterinarians [11,13]. Therefore, a simple, accurate and noninvasive technique is required to determine the presence of ESGD.…”
Section: Introductionmentioning
confidence: 99%